Silver nanorod-induced porous networks: A pathway to efficient thermal energy transfer via pool boiling heat transfer - Nurettin Sezer (14778217) (2023)
With the continuous trend of miniaturization in the electronics sector, high heat flux management is becoming increasingly important for ensuring efficient and safe operation. For thermal management of high heat flux devices, nucleate boiling is a prominent passive heat transfer approach. The two fundamental variables that can be varied to improve the effectiveness and capacity of the nucleate boiling process are the working fluid and surface properties such as surface roughness, wettability, area, and capillary. Boiling-induced interconnected porous network of silver nanowires coating is identified in this research as an efficient coating for enhanced nucleate boiling performance. The maximal ability of heat transmission, known as critical heat flux, and the efficiency of the boiling heat transfer process, represented by the heat transfer coefficient, are explored for the newly developed surfaces. Using a nucleate boiling testing setup, three distinct concentrations of silver nanowires-based nanofluids, 0.01%, 0.001%, and 0.0001%, were examined as working fluid. The working fluid resulted in the deposition of the nanowires over the heating surface and resulted in enhanced heat transfer performance. The maximum enhancement of 200% and 93.7% has been reported for critical heat flux and heat transfer coefficient, compared to deionized liquid on the unmodified Cu substrate. A detailed characterization has been performed to investigate the topology, wettability and morphology of the surfaces and understand the enhancement mechanisms. Other Information Published in: Case Studies in Thermal Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.csite.2023.102849